Ani: An urban planning idea for the New City and its continuity - Baeva, Olga (project baikal, 2023)
The spatial composition of Ani, which used to be a large medieval town and the capital of Armenia, is analysed in the context of the general principles of medieval urban planning. The analysis made it possible to reveal the spatial relationship of urban dominants, to raise a question of the original idea of the architect Trdat and its continuity in subsequent periods of the city’s history.
Keywords: Ani; architecture; Trdat; medieval city; history of urban planning